1995
DOI: 10.1063/1.115072
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering characterization of the crystalline qualities of ZnSe films grown on S-passivated GaAs(100) substrates

Abstract: A comparative study of the Raman spectra of ZnSe films grown by molecular beam epitaxy on GaAs(100) substrates passivated by NH4)2)Sx and S2Cl2 solutions is presented. Based on the analysis of the line shape of the first-order longitudinal-optical phonon of ZnSe with spatial correlation model of Raman scattering, it is shown that the ZnSe films grown on the GaAs substrates passivated by S2Cl2 solutions have longer coherence lengths, which indicate that their crystalline qualities are better than those passivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Since the spectra could not fit with only the CZTS and CZTSe peaks, we conclude that secondary phases are present, indicated by the peaks at 250 cm -1 , 276 cm -1 and 352 cm -1 . These phases are identified as ZnSe (253 cm -1 ) [10] and ZnS (271 cm -1 , 352 cm -1 ) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since the spectra could not fit with only the CZTS and CZTSe peaks, we conclude that secondary phases are present, indicated by the peaks at 250 cm -1 , 276 cm -1 and 352 cm -1 . These phases are identified as ZnSe (253 cm -1 ) [10] and ZnS (271 cm -1 , 352 cm -1 ) [11].…”
Section: Discussionmentioning
confidence: 99%
“…It's found that using S 2 Cl 2 as a passivation solution for ZnSe/GaAs has better crystalline quality compare to the (NH 4 ) 2 S x due to the longer process time. The Raman spectra of ZnSe/GaAs also showed peak at 205, 253 cm -1 for ZnSe and 268, 291 cm -1 for GaAs [5]. The high quality of crystalline can be achieved when the temperature is higher than 475 o C for chromium dope ZnSe film deposited on sapphire [4].…”
Section: Introductionmentioning
confidence: 91%
“…When the excited light penetrates deeper than the thickness of the depletion layer, LOPC mode will be measured. Therefore, an effective passivation can cause a decrease in the LO peak intensity and an increase of the LOPC peak intensity [15][16][17]. In order to further demonstrate the effect of ODT passivation, especially the stability of air exposure, we prepared three groups of samples for Raman spectral analysis: unpassivated, ODT passivated and exposure in air for 3 days after ODT passivation respectively, as shown in Figure 2ac.…”
Section: Introductionmentioning
confidence: 99%
“…When the excited light penetrates deeper than the thickness of the depletion layer, LOPC mode will be measured. Therefore, an effective passivation can cause a decrease in the LO peak intensity and an increase of the LOPC peak intensity [15][16][17]. It can be seen from Figure 2 that the passivation changed the balance between the LOPC (265 cm −1 ) peak and the LO (288 cm −1 ) peak.…”
Section: Introductionmentioning
confidence: 99%